EVALUASI KUALITAS BIBIT PALA (Myristica fragrans Hout) DI DESA RUMAHKAY KECAMATAN AMALATU KABUPATEN SERAM BAGIAN BARAT - Ines Tuamely; Johan Riry; Ferdinand Salomo Leuwol (JURNAL HUTAN PULAU-PULAU KECIL, 2023)
Nutmeg (Myristica fragrans Hout) is a plantation crop that has high economic value. Good growth of nutmeg must be started from using good seeds and to get good seeds, the seeding technique must use good quality seeds and good shade. The people of Rumahkay Village use different shelters for seeding nutmeg seedlings, for this reason it is necessary to evaluate which type of shade is better. The purpose of this study was to determine the effect of the type of shade on the growth of nutmeg seedlings, to determine which type of shade is the best. This research was carried out from August 2022 to September 2022 in Rumahkay Village, Amalatu District, West Seram Regency. This experiment was a completely randomized design (CRD) consisting of 8 levels of shade treatment (N0=no shade; N1=zeng; N2= plastic; N3= paranet; N4=roof house; N5= sago leaves; N6= mosquito net and N7= banner) which was repeated 4 times. Parameters measured were plant height, stem diameter, number of leaves and total leaf area. The results of the analysis show that the type of shade treatment has a significant and not significant effect on all observation parameters. The results of the Fisher LSD 95% test showed that the shade type N3 (70% paranet) produced the best nutmeg seeds compared to other types of shade.